2019
DOI: 10.1101/583328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reinforcement regulates timing variability in thalamus

Abstract: the project. J.W. and E.H. collected the main behavioral and electrophysiology data. J.W. analyzed the data and developed the model. E.H. played a major role in data analysis. J.W and M.J. interpreted the data with contribution from E.H. and N.M.. N.M. performed and analyzed the control experiment in a third monkey, and highlighted the need for additional validation analyses. A.A. conducted the human psychophysics experiments. M.J. supervised the project. All authors contributed to the writing of the manuscrip… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 130 publications
(149 reference statements)
0
5
0
Order By: Relevance
“…There are several reasons why this is a useful paradigm for investigating information integration in the central thalamus. First, multiple lines of evidence across species suggest a central role for the central thalamus in timing movements (Tanaka, 2006;Lusk et al, 2020;Wang et al, 2020). Second, the authors can leverage their own prior investigations of signals in cerebellar nuclei and striatum (Ohmae et al, 2013;Kameda et al, 2019) to determine which components of thalamic activity might rely on these dominant inputs to the central thalamus.…”
mentioning
confidence: 99%
“…There are several reasons why this is a useful paradigm for investigating information integration in the central thalamus. First, multiple lines of evidence across species suggest a central role for the central thalamus in timing movements (Tanaka, 2006;Lusk et al, 2020;Wang et al, 2020). Second, the authors can leverage their own prior investigations of signals in cerebellar nuclei and striatum (Ohmae et al, 2013;Kameda et al, 2019) to determine which components of thalamic activity might rely on these dominant inputs to the central thalamus.…”
mentioning
confidence: 99%
“…Importantly, Cheng et al (2007) highlighted that the transition to a dopamine-insensitive state was similar to general observations of striatal neurons becoming silent once a reward becomes predictable with training (Schultz, 1998). Similarly, Wang et al (2020) recently suggested that the noise in corticostriatal circuits that underlies timing variability is subject to adjustments through reinforcement learning. This overlap between learning and timing may help to reconcile our seemingly discrepant results.…”
Section: Discussionmentioning
confidence: 98%
“…At the same time, all BN-ROIs overlapped with FEN and TRC masks showed a gradual increase only in the variance of the averaged BOLD signal. Such multidirectional changes in variance may indicate different information processing in the cortical and subcortical areas (Wang et al, 2019).…”
Section: Changes In the Variance Of The Bold Signal After Fear Learnimentioning
confidence: 99%